KORELASI PERAN KELUARGA TERHADAP PENYESUAIAN DIRI REMAJA - Juli Andriyani (Jurnal Al-Bayan: Media Kajian dan Pengembangan Ilmu Dakwah, 2016)
ABSTRACT: There are some teens who have failed in the adjustment itself, such as inability to undertake real appearance, unable to adapt to a variety of groups, can not interact socially with the community, can not accept his situation. This failure was provoked by a problem with the family, such as economic status of parents down to the middle, the parents are very busy at work, parents who are less attentive to their children, parents who are too authoritarian, causing the child lacks self-esteem, no confidence , academic achievement is low, less able to hang out with friends, having problems when adjustments with friends that the economic status of their parents upper middle, the child became naughty, hostility, anxiety, and aggressive.The purpose of this study to determine the extent of the role of family environment on the adolescent ctadjustment.. This research uses quantitative methods. The independent variable is the family environment and the dependent variable is the adjustment. Subjects numbered 125 respondents were selected using random sampling techniques. In collecting the data, researchers used the method in the form of Likert scale. Data analysis using correlation techniques Product Moment Karl Person, with SPSS version 17.0 for Windows. Based on the results of data analysis in this study obtained the r value of 0.769 and significance of P = 0.000 (P